Regional Head of Performance Accountability in Local Government Law from The New Order to The Reform Era - Agus Budi Santoso (Varia Justicia, 2021)
The accountability of regional heads is one of the benchmarks for the success of development and regional autonomy. This study aims to analyze the accountability of regional heads in each law. The research method used is a normative juridical method with a statutory approach based on a study of statutory regulations related to this research topic. The results showed that the accountability of regional heads in Law Number 5 of 1974 is not regulated. However, the characteristics of the new post-reform decentralization order by a centralized government were marked by the enactment of Law Number 22 the Year 1999. The DPR elects regional heads based on accountability. In addition, regional heads can be dismissed by the DPR if their accountability report (LPJ) is rejected, which in turn creates political instability. It is also due to the absence of a parallel position between the regional head and the DPRD.